Wavelet-based modal analysis for time-variant systems. (January 2015) - Dziedziech, K.; Staszewski, W.J.; Uhl, T.
Abstract: The paper presents algorithms for modal identification of time-variant systems. These algorithms utilise the wavelet-based Frequency Response Function, and lead to estimation of all three modal parameters, i.e. natural frequencies, damping and mode shapes. The method presented utilises random impact excitation and signal post-processing based on the crazy climbers Algorithm. The method is validated using simulated and experimental data from vibration time-variant systems. The results show that the method captures correctly the dynamics of the analysed systems, leading to correct modal parameter identification. Highlights: A new method for the analysis and identification of time-variant vibration systems is proposed. The method utilises the wavelet-based Frequency Response Function (FRF). Random impact excitation is used to obtain the wavelet-based FRF. Signal post-processing – based on ridge extraction and the crazy climbers Algorithm – is applied to identify modal parameters, i.e. natural frequencies, damping and mode shapes. The method captures the dynamics of the analysed simulated and experimental time-variant vibration systems. All modal parameters - and their evolution in time - are identified correctly.